CHILDREN ACUTE ENTERIC INFECTIONS IN PAEDIATRICIAN PRACTICE: POSSIBILITIES OF DIAGNOSTICS AND THERAPY - D. V. Usenko; А. А. Ploskireva; A. V. Gorelov (Вопросы современной педиатрии)
Acute Enteric Infections (AEI) occupy one of the leading places in structure of infectious pathology at children's age. A variety of etiological agents (bacteria, viruses and protozoa) causing infectious diarrhoea, the high frequency of mixed infections, frequent failures and uneven course prove the necessity of search of ways for optimization of diagnostic and therapeutic approaches according to modern scientific data. The principles of clinical and laboratory diagnostics of AEI are considered in the article. Criteria of the assessment of a disease severity, predictive criteria of development of the life-threatening states connected with the exicosis are presented. The principles of AEI treatment are presented from the modern positions, the necessity of an integrated approach and staging in therapy with the personified choice of preparations considering weight, phase and clinical form of a disease, age of a child and a macroorganism condition by the time of the disease beginning are introduced. The necessity of a strictly differentiated approach to prescription of antibiotics is emphasized. The data on expediency of inclusion of probiotics to starting AEI therapy of virus aetiology are separately presented taking into account strain-specific efficiency that provides the reliable reduction of degree of intensity and duration of the main symptoms of a disease, and also has beneficial impact on a condition of microflora of a gastrointestinal path.